EVALUATION OF ATYPICAL HYPERPLASIA AFTER PERCUTANEOUS VACUUM-ASSISTED BIOPSY OF SUSPICIOUS CALCIFICATIONS - Aguillar, Vera Lucia Nunes; Mello, Giselle Guedes Netto de; Tucunduva, Tatiana de Melo Cardoso; Aracava, Marcia Mayumi; Oliveira, Elisandra Cristina (Mastology, 2020)
Introduction: Atypical ductal hyperplasia (ADH), atypical lobular hyperplasia (ALH), lobular carcinoma in situ (LCIS), and flat epithelial atypia (FEA) are part of a heterogeneous group of lesions with uncertain malignant potential and varying rates of malignancy after wide excision. They represent a clinical challenge, given the lack of well-defined approach recommendations. Objective: To determine the local rate of “upgrade” to malignancy (invasive carcinoma or in situ) after wide excision of ADH, ALH, LCIS (classic lobular neoplasia) diagnosed by percutaneous vacuum-assisted biopsy performed only in suspicious calcifications, as well as analyze radiological and histopathological parameters that can be associated with a higher risk of “upgrade”. Material and Methods: This is a retrospective analysis of 117 patients diagnosed with ADH, LCIS, and FEA after percutaneous vacuum-assisted biopsy of suspicious calcifications, from 2015 to 2018. We evaluated radiological parameters – lesion size, morphology of the calcifications, diameter of the needle, and presence of residual calcifications – and histopathological parameters – extension of atypia (focal or multifocal) and association with other atypias. Results: Among the 106 patients included, 77 (73%) underwent surgery, with a rate of “upgrade” to malignancy of 19.5% (10 ductal carcinomas in situ, of which 30% had high grade) and 5 had invasive carcinomas (4 ductal and 1 tubular, all with low grade). In the subgroup analysis, the rate of “upgrade” was 31% for ADH, 14.7% for FEA, and 7.7% for LCIS. Needle diameter (9Gx11G) (p=0.48), presence of residual calcifications (less than 90% of the cluster removed) (p=0.73), and mean cluster extension (calculated based on the original mammography) (p=0.66) showed no statistically significant correlation with an increase in the rate of “upgrade”. Amorphous calcifications predominated (60%), followed by fine pleomorphic ones, with rates of “upgrade” of 11% and 35%, respectively. Regarding histological parameters, we found no statistically significant difference between groups with focal (up to 2 foci) and multifocal atypia or association with other atypias. Conclusion: Our rate of “upgrade” to malignancy was similar to that of the published literature, and we found no statistically significant radiological or histological criteria for a greater risk of “upgrade”.